RETRACTED: Transcriptome Analysis Reveals the Expressed Gene Complement and Acute Thermal Stress Response of Acropora digitifera Endosymbionts - Ravelo, Stephanie Faith; Posadas, Niño; Conaco, Cecilia (Frontiers in Marine Science, 2022)
Dinoflagellate endosymbionts from the family Symbiodiniaceae form a mutualistic relationship with corals. However, this partnership is vulnerable to temperature stress, which can result in coral bleaching. In this study, we sequenced the metatranscriptome of symbionts (dominated by ITS2 type C3u) associated with the common scleractinian coral, Acropora digitifera, from Bolinao, Pangasinan, northwestern Philippines, to elucidate their genetic complement and stress response mechanisms. The assembled metatranscriptome revealed a rich repertoire of genes for the utilization of nutrients and metabolic exchange with the host, as well as genes that provide protection against cellular damage. Exposure of the algal endosymbionts to 31°C for 12 h induced global changes in the transcriptome profile. While transcripts involved in cell signaling, cytoskeletal organization, and rRNA processing were upregulated, downregulation of transcripts related to translation, proteolysis, lipid storage, and immune response indicate vulnerability to acute thermal stress. Some of these stress responsive transcripts were predicted to be under microRNA (miRNA) regulation. These findings reveal conserved hallmarks of coral-algal symbiosis and provide insights into the genetic potential and acute thermal stress response of a common symbiont of corals in the region.